Turmeric: The yellow allergen - Vijayasankar Palaniappan; Kaliaperumal Karthikeyan (Indian Dermatology Online Journal, 2023)
Turmeric is the dried rhizome of Curcuma longa Linn which is extensively used in Indian culture. Curcumin is its most active pharmaceutical component. Turmeric use is very closely related with the socio-religious life of the population. Topical application of turmeric is a very common practice in the daily lives and auspicious occasions in South India. However, the allergenic potential of this commonly used spice is mentioned in various case reports and studies. The dermatologists and patients should be aware of the possible allergic reactions of this widely used herb. The purpose of this review is to give a brief overview of allergenic potential of this commonly used spice.